ANALISIS PENAFSIRAN AYAT AYAT TENTANG BUAH BUAHAN DALAM TAFSIR AL-QUR’AN - Destia Vani; Rindu Permatasari; Ali Akbar (PT. Hasba Edukasi Mandiri, 2025)
This article examines the text and context of rerses about fruits in the Qur'an. Verses about fruits are scattered in various verses as an affirmation of the importance of these fruits. This study asest What are the verses about fruits, and how are they interpreted? To answer the research question, qualitative methods explore and find the interpretations used as primary sources. The findings of this study explain that there are 6 (six) fruits mentioned in the Qur'an, namely bananas, figs, olives, dates, pomegranates and grapes, which are scattered in various verses. Interpretations of verses about fruits generally refer to the understanding that fruits are a sign and signal of the greatness of Allab. In addition, some specifically refer to fruits that are known today.